(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Technology is now rapidly becoming crucial for the development of India. Now, everything and everyone is getting digitalized, whether it is private sector, public sector or even an individual. Most of the organizations have understood the prospective of digital marketing in India. They understood its time utility, cost effectiveness and efficiency. Actually, Digital marketing is the marketing of goods and services using various technologies to capture the new customers and contain the existing one for various products. It is making the task of marketing much easier for any organization. It is helping them to understand their customers. They can now get immediate feedback about their products. Now, the digitalization is giving an opportunity to the consumers and producers to communicate with each other. This approach of marketing is taking customer satisfaction to the next level. Now, consumers themselves are making their own product for the producers by giving their valuable suggestions continuously. The research focus is to analyse the various aspects of digital marketing and its impact on consumers, companies and the development of the country.